2021
DOI: 10.5194/acp-2021-42
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reactive nitrogen around the Arabian Peninsula and in the Mediterranean Sea during the 2017 AQABA ship campaign

Abstract: Abstract. We present ship-borne measurements of NOx (≡ NO + NO2) and NOy (≡ NOx + gas- and particle-phase organic and inorganic oxides of nitrogen) in summer 2017 as part of the expedition Air Quality and climate change in the Arabian Basin (AQABA). The NOx and NOz (≡ NOy–NOx) measurements, made with a thermal dissociation cavity-ringdown-spectrometer (TD-CRDS), were used to examine the chemical mechanisms involved in the processing of primary NOx emissions and their influence on the NOy budget in chemically d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…In some (especially marine) environments (Osthoff et al, 2008;Kercher et al, 2009), loss of N2O5 to particles can result in formation of ClNO2 (R18) which, via photolysis, reforms NO2 the next day. The above reactions illustrate that NOx and VOCs provide the catalyst and fuel for photochemical ozone formation, the efficiency of which is determined by the competition between photolysis of NO2 to ozone and its conversion to NOz (Day et al, 2003;Wild et al, 2014;Wild et al, 2016;Womack et al, 2017). Modelling studies have identified the Arabian Gulf as a hotspot for O3 pollution and photochemical smog, with O3 mixing ratios exceeding 100 ppbv (Lelieveld et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In some (especially marine) environments (Osthoff et al, 2008;Kercher et al, 2009), loss of N2O5 to particles can result in formation of ClNO2 (R18) which, via photolysis, reforms NO2 the next day. The above reactions illustrate that NOx and VOCs provide the catalyst and fuel for photochemical ozone formation, the efficiency of which is determined by the competition between photolysis of NO2 to ozone and its conversion to NOz (Day et al, 2003;Wild et al, 2014;Wild et al, 2016;Womack et al, 2017). Modelling studies have identified the Arabian Gulf as a hotspot for O3 pollution and photochemical smog, with O3 mixing ratios exceeding 100 ppbv (Lelieveld et al, 2009).…”
Section: Introductionmentioning
confidence: 99%